PEMBERDAYAAN PEREMPUAN MELALUI PREVENTIF EDUKASI TENTANG KANKER LEHER RAHIM - Rita Yulifah; Tri Johan Agus Yuswantoro (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2021)
Mortality rate due to cervical cancer is quite high, namely 20-25 deaths / day. This community service activity was carried out at the Sumberjo Village Women's School, Bumiaji District, Batu City with a total target of 30 mothers. The service method is carried out in two stages, namely: the first stage provides education in the form of training to members of the Village Women's School about cervical cancer, the second stage provides skills on making cancer-preventing foods. Before and after the target activity was given a pretest and posttest questionnaire. The results of the pretest 70% did not understand, 23.3% understood and 6.7% very well understood. After being given education 16.7% understood and 83.3% very understood. The results of preventive action resulted in 6 healthy menus prepared from the basic ingredients of vegetables and fruits produced by the community. Empowering women through education about cervix cancer is felt to be very beneficial. Educational preventive activities can increase the understanding of village women and healthy living habits, especially in terms of food consumption in an effort to prevent or minimize the occurrence of morbidity and mortality due to cervical cancer.